2021
DOI: 10.1038/s41598-021-98848-2
|View full text |Cite
|
Sign up to set email alerts
|

Capacity differences in working memory based on resting state brain networks

Abstract: Herein, we compared the connectivity of resting-state networks between participants with high and low working memory capacity groups. Brain network connectivity was assessed under both resting and working memory task conditions. Task scans comprised dual-task (reading sentences while memorizing target words) and single-task (reading sentences) conditions. The low capacity group showed relatively stronger connectivity during resting-state in most brain regions, and the high capacity group showed a stronger conn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 55 publications
0
1
0
Order By: Relevance
“…The importance of the frontal cortex was also suggested in our previous study (Osaka et al, 2021), which investigated individual differences in WM capacity based on brain RSN. Additionally, our investigation revealed that capacity differences in working memory, assessed through a reading span test, which is one of the complex span tests, are linked to differences in the strength of RSN connectivity in the brain.…”
Section: Discussionmentioning
confidence: 68%
“…The importance of the frontal cortex was also suggested in our previous study (Osaka et al, 2021), which investigated individual differences in WM capacity based on brain RSN. Additionally, our investigation revealed that capacity differences in working memory, assessed through a reading span test, which is one of the complex span tests, are linked to differences in the strength of RSN connectivity in the brain.…”
Section: Discussionmentioning
confidence: 68%
“…Therefore, this part of the brain is probably important for ASD pathophysiology. As we know that the dorsolateral prefrontal cortex plays an important role in executive function by connecting the frontal and parietal cortices via frontoparietal networks ( Haber et al, 2021 ), enhancing working memory capacity ( Osaka et al, 2021 ), and is related to human intelligence ( Hearne et al, 2016 ). An irregular arrangement of neural connections is one of the proposed pathologies of ASD.…”
Section: Discussionmentioning
confidence: 99%